CONTAMINAÇÃO POR BISFENOL A (BPA) NA INFÂNCIA: ALTERAÇÕES CARDIOVASCULARES E O PAPEL PROTETOR DO KEFIR - Friques, Andreia Gomes Freitas (2019)
Although the harmful effects of Bisphenol A (BPA) contamination in infancy has been demonstrated, the mechanisms of action of cardiovascular outcomes still is scant. Here, we demonstrate the effects of BPA in infancy and the protective action of kefir. Me